The Influence of Efficiency and Effectiveness on the Performance of Apron Movement Control in Supervising Aircraft Movement at Sultan Thaha Saifuddin Airport Jambi - Sthevani Dwi Ananda; Kartika Fajar Nieamah (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
The success of employees in carrying out their duties can be measured through the timeliness in servicing the aircraft that will park on the apron that will use the Aviobridge because at Sultan Thaha Saifuddin Airport Jambi the operation of the Aviobridge is carried out by Apron Movement Control (AMC) personnel. When the number of service delays decreases, the target achieved will be optimal. The case that the researchers observed was that currently the personnel in the Apron Movement Control (AMC) unit of Sultan Thaha Saifuddin Jambi Airport did not meet the number specified in the nomenclature. In accordance with the directors' regulation no PD.01.01/08/2018/0070 regarding the Airside operation formation, it is explained that the number of personnel that should be there is 11 people. Meanwhile, there are only 6 personnel in the Apron Movement Control (AMC) unit. The purpose of this study was to find out how much influence efficiency and effectiveness have on the performance of Apron Movement Control (AMC) in supervising aircraft movements on the apron of Sultan Thaha Jambi Airport. Data collection was carried out through distributing questionnaires in quantitative research with purposive sampling techniques and a sample of 40 respondents. Using SPSS 25. Based on the results of the study, it showed that the independent variables (efficiency and effectiveness) had an effect on the dependent variable (AMC performance) in supervising aircraft movements at Sultan Thaha Saifuddin Airport, Jambi. The R Square value of 0.751 means that the efficiency and effectiveness variables affect the performance of Apron Movement Control (AMC) by 75.1%.